Estimated cost of VEGFR TKI associated adverse events in metastatic renal cell carcinoma patients - Jeffrey Thomas Yorio; Aviva G. Asnis-Alibozek; Vijay Kasturi; Thomas E. Hutson (BMC, 2024)
Abstract Introduction The majority of metastatic renal cell carcinoma (mRCC) patients receive one or more VEGFR TKI agents, alone or in combination with an immune-oncology (IO) agent or an mTOR inhibitor. To date, the cost of adverse events (AEs) common to VEGFR TKIs has not been quantified. This study estimated the potential impact of differences in VEGFR TKI AE profiles on treatment cost efficiency in the relapsed/refractory (R/R) setting. Methods Patients with documented mRCC who were treated with VEGFR TKI therapies between Jan 2015 and Mar 2021 were identified using EMR. ICD-10 diagnosis codes were used to identify the first occurrence of each class effect AE. Patients were matched to 3rd party insurance claims, and costs associated to TKI AEs within 90 days of index event were captured. Average per patient AE cost data was calculated and applied to published incidence data to estimate regimen-specific AE total cost burden within a hypothetical commercial plan for mRCC patients undergoing treatment in the R/R setting. Results The highest total cost for AE management was attributed to lenvatinib and everolimus use at $13,303, followed closely by sunitinib at $13,092. Tivozanib treatment was associated with the lowest total cost of AE management at $7,523, driven by the relatively lower incidence of certain high-cost AEs. Conclusions The estimated costs of managing VEGFR TKI class-effect AEs were lowest with tivozanib, and highest with lenvatinib and everolimus, indicating potentially differential healthcare resource burden by TKI regimen. The use of tivozanib in the 3 L + mRCC setting suggests potential costs offsets when compared to other TKI regimens.